Нелинейные преобразования гладких мер на бесконечномерных пространствах - Кулик, А.М.; Пилипенко, А.Ю. (Український математичний журнал, 2000)
Досліджуються властивості образу диференційовної міри на нескінченновимхрному банаховому просторі при нелінійних перетвореннях простору. Доведено загальний результат про абсолютну неперервність цього образу відносно вихідної міри, отримано формулу для щільності, аналогічну до формули Рамера - Кусуоки для перетворень гауссової міри. Доведено абсолютну неперервність образу для класів перетворень, які мають додаткові структурні властивості, а саме, узгоджених, моиотоиих, породжених диференціальним потоком. Останні застосовуються для реалізації методу характеристик розв'язання нескіпченновимірних рівнянь з частинними похідними першого порядку та лінійних рівнянь із розширеним стохастичпим інтегралом за даною мірою. We investigate the properties of the image of a differentiable measure on an infinitely-dimensional Banach space under nonlinear transformations of the space. We prove a general result concerning the absolute continuity of this image with respect to the initial measure and obtain a formula for density similar to the Ramer–Kusuoka formula for the transformations of the Gaussian measure. We prove the absolute continuity of the image for classes of transformations that possess additional structural properties, namely, for adapted and monotone transformations, as well as for transformations generated by a differential flow. The latter are used for the realization of the method of characteristics for the solution of infinite-dimensional first-order partial differential equations and linear equations with an extended stochastic integral with respect to the given measure.